2009
DOI: 10.1007/s00535-009-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

−651C/T promoter polymorphism in the CD14 gene is associated with severity of acute pancreatitis in Japan

Abstract: -651C/T promoter polymorphism in the CD14 gene was associated with severity of AP in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Pancreatic tumours are known to be highly hypoxic and hypoxia has been found to induce PSC activity, migration, and activation (51,143,182). Decreased activity and expression of PAK1 in the pancreatic orthotopic tumours in PAK1 KO mouse resulted in increased mouse survival (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Pancreatic tumours are known to be highly hypoxic and hypoxia has been found to induce PSC activity, migration, and activation (51,143,182). Decreased activity and expression of PAK1 in the pancreatic orthotopic tumours in PAK1 KO mouse resulted in increased mouse survival (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…OR, odds ratio; BFDP, Bayesian false-discovery probability; AP, acute pancreatitis; RAP, recurrent acute pancreatitis. Two articles 34,35 reported on the functional c.194+2T>C (IVS3+T>C, rs148954387) variant, but found no association. Meta-analysis of these studies confirmed this association in the overall population (3 studies) (OR 7⋅51, 95 per cent c.i.…”
Section: Serine Protease Inhibitor Kazal Type 1 (Spink1)mentioning
confidence: 99%
“…1,2 Genetic factors predisposing for the development and progression of AP are largely unknown. 3,4 Because pancreatic protease/antiprotease plays pivotal roles in the pathogenesis of pancreatitis, genetic studies have focused on this system, especially in patients with chronic pancreatitis (CP). For example, p.R122H (c.365G > A) and p.N29I (c.86A > T) mutations in the cationic trypsinogen (PRSS1) gene are responsible for hereditary pancreatitis.…”
Section: Introductionmentioning
confidence: 99%